From Pb to Bi: A Promising Family of Pb-Free Optoelectronic Materials and Devices - Wu, Cuncun; Zhang, Qiaohui; Liu, Ganghong; Zhang, Zehao; Wang, Duo; Qu, Bo; Chen, Zhijian; Xiao, Lixin (ADVANCED ENERGY MATERIALS, 2020)
Lead-based organic-inorganic hybrid perovskite materials are widely used in optoelectronic devices due to their excellent photophysical properties. However, the main issues which hinder its commercialization are the toxicity caused by lead and the intrinsic instability of the material. Recently, many lead-free halide materials with good intrinsic stability have been reported, among which bismuth-based halide materials have attracted extensive research due to their structure and promising optoelectronic properties. In this review, bismuth-based materials are divided into binary BiX3 (X = I, Br, Cl), ternary A(a)Bi(b)X(a)(+3)(b) (A = Cs, Rb, MA, Ag, etc.), and quaternary A(2)AgBiX(6) (A = Cs, Rb, MA, etc.) according to its elemental composition. The structure and optoelectronic properties of bismuth-based halide materials, which may be helpful for the development of bismuth-based halide materials and lead-free perovskites in the future, are summarized and highlighted.